Pengaruh Variasi Mutu Baja Tulangan Pada Penampang Balok Beton Bertulang - Riza Aryanti (Universitas Andalas, 2024)
Reinforced concrete beams are important structural elements in building construction that function to channel loads from floor slabs to supporting columns. When receiving a load, reinforced concrete beams experience two conditions, namely compression and tension. Reinforced concrete beams are basically made of a combination of plain concrete that is able to withstand compression forces and reinforcing steel that is able to withstand tensile forces. The amount of reinforcing steel installed on the beam is adjusted to the load applied so that the beam is able to withstand the load. In addition to the amount of reinforcement used, the quality of the steel used also affects the capacity of the beam. This study aims to analyze the variation in the quality of reinforcing steel on moment-curvature, ductility, concrete stress distribution and neutral axis depth. The analysis was carried out using RCCSA v4.3 software. The width of the beam cross-section is 350 mm and the height of the beam cross-section is 700 mm. The quality of concrete (fc') used is 30 MPa. The variation in the quality of reinforcing steel (fy) is respectively 300 MPa, 350 MPa, 400 MPa, 450 MPa, 500 MPa and 550 MPa. The analyzed reinforced concrete beams are single reinforced concrete beams. The results of the study indicate that variations in the quality of reinforcing steel affect the moment-curvature, ductility, depth of the concrete compressive stress block and neutral axis depth but do not affect the maximum concrete compressive stress value in the concrete compressive stress block.